The Art of Resiliency: Patient Stories of Maternal Mental Health Experiences - Sara Santarossa; Becca Austin; Molly A. Bell; Samantha C. Henry; Ashley Inclima; Hailey Maddox; Tara G. Smith; Leah Copeland; Dana Murphy; Ashley Redding; Amy Loree (Journal of Patient-Centered Research and Reviews)
As part of a Patient-Centered Outcomes Research Institute Eugene Washington Engagement Award aimed at improving capacity to address maternal mental health in research, this collection of stories describes experiences from six unique patient perspectives. Using motherhood as a common thread, these six stories weave together the patients’ challenges and barriers juxtaposed with their hopes and dreams. Exploring such topics as infant loss, expectations versus the reality of the postpartum experience, grief, loss of identity, loss of physical or emotional safety, advocacy, and perseverance through challenging maternal mental health experiences, these tales of resiliency leverage the voices and lived experiences of patients in a powerful, reflective manner.